Effect of molecular weight on the properties and organic solar cell device performance of a donor–acceptor conjugated polymer1. Issue 12 (28th March 2015) - Xiao, Zeyun; Sun, Kuan; Subbiah, Jegadesan; Qin, Tianshi; Lu, Shirong; Purushothaman, Balaji; Jones, David J.; Holmes, Andrew B.; Wong, Wallace W. H.
<x xml:space="preserve">Abstract</x> The effect of molecular weight of a conjugated polymer on its photophysical properties and solar cell device performance was investigated.